Nanostructured titanium dioxide thin film for dye-sensitized Solar cell applications - Ahmad, Mohd Khairul (2009)
Nanostructured Titanium Dioxide (TiC^) thin film for Dye-Sensitized Solid State Solar Cell (DSSSC) application has been synthesized using sol-gel method and deposited onto silicon and glass substrates using spin coating technique. The optimized annealing temperature and sol-gel concentration were obtained a| 500°C and 0.2M, respectively. Basically, there were four properties studied; surface morphology, structural, electrical and optical properties. Field Emission Scanning Electron Microscopy (FE-SEM) / Scanning Electron microscopy (SEM) were carried out to observe the changes in surface morphology whenever there are changes on the parameters. X-Ray Diffractions (XRD) characterization of the samples was taken to examine the TiC>2 crystalline phases and the intensity of nanocrystalline particles in the thin film. I-V measurement using two-point probe equipment was used to observe the electrical properties which include the measuring of the sheet resistance, the resistivity and the conductivity of the TiC>2 thin film. The optical properties were observed using UV-Vis-NIR spectrophotometer. The thin film transmittance and the band gap energy were also observed using this spectrophotometer. At the end of this research, uniform and homogeneous TiC>2 thin film has successfully prepared. By controlling the sol-gel concentration, a transparent TiC>2 thin film has been developed which has high transmittance property of above 80%. The TiC>2 thin films which were annealed at a temperature of 500°C and prepared at 0.2M of sol-gel precursor concentration gave the optimum results. By adding TiC>2 nanopowder, the surface area and porosity of TiC>2 thin film is improved, thus good candidate to use in DSSSC application.